Economic development - Todaro, Michael P.; Smith, Stephen C. (United Kingdom : Pearson Education, 2015)
The leading textbook in this field - provides students with a complete and balanced introduction to the requisite theory, driving policy issues, and latest research. Todaro and Smith take a policy-oriented approach, presenting economic theory in the context of critical policy debates and country-specific case studies, to see how theory relates to the problems and prospects of developing countries.
Part 1: Principles and concepts -- 1.Introducing economic development: a global perspective -- 2.Comparative economic development -- 3.Classic theories of economic growth and development -- 4.Contemporary models of development and underdevelopment -- Part 2: Problems and policies: domestic -- 5.Poverty, inequality, and development -- 6.Population growth and economic development: causes, consequences and controversies -- 7.Urbanization and rural-urban migration: theory and policy -- 8.Human capital: education and health in economic development -- 9.Agricultural transformation and rural development -- 10.The environment and development -- 11.Development policymaking and the roles of market, state, and civil society -- Part 3: Problems and policies: international and macro -- 12.International trade theory and development strategy -- 13.Balance of payments, debt , financial crises, and stabilization policies -- 14.Foreign finance, investment, aid, and conflict: controversies and opportunities -- 15.Finance and fiscal policy for development.
Includes index.
Keywords: DEVELOPING COUNTRIES